Line and Grid Impedance Impact on the Performances of a Parallel Connected Modular Inverter System - Tahar Zebbadji; Seddik Hadji; Rachid Ibtiouen (Institute of Advanced Engineering and Science, 2015)
With the rising fuel cost, increasing demand of power and the concerns for global climate change, the use of clean energy make the connection of power electronics building bloc in the heart of the current research. The high output current applications make the parallel connection of modular inverters to be a solution for the use of low power building block inverters where the output power cannot be handled by a single inverter configuration. In this context, average-modeling using average phase–leg technique allows the n-parallel connected inverters to be analyzed accurately and rapidly without requiring the complexity of the full switched inverter topology. The obtained analytical solution along with the equivalent circuit model makes easier the design of the control loop. The analytical solution of the n-parallel connected inverters shows the impact of the line and grid impedance on the performance of the overall system. The impact of this coupling has to be investigated such that the main feature of paralleling inverters is guaranteed and that the inverter mode of operation will not be compromised. The main advantage of paralleling inverters can be lost for a certain coupling impedance considerations.